2021
DOI: 10.1111/2047-3095.12347
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the evidence‐based practice research field in nursing from 1995 to 2021: A bibliometric analysis

Abstract: Background: Evidence-based nursing and its practices are increasing rapidly in the health and nursing literature. A holistic image of evidence-based nursing research is needed to address evidence-based studies and available information on nursing. Aim:The aim of this study was to evaluate evidence-based nursing-related research with bibliometric analysis in order to provide a structured macroscopic overview of its features and advances. Methods: A bibliometric analysis of 4,159 publications from 1995 to 2021 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…[22] Comprehensive nursing based on the concept of evidence-based nursing can dialectically understand the problems existing in clinical practice and propose humanized and targeted nursing measures through analysis and summary, which are of important for reducing patients' pain and improving their quality of life. [23] In this study, the incidence of postoperative pressure ulcers was considerably lower in the observation group than in the control group, indicating that perioperative comprehensive nursing care can significantly reduce the incidence of pressure ulcers in prone patients. Evaluation of the patient risk factors for pressure ulcers is a key factor in their prevention.…”
Section: Discussionmentioning
confidence: 49%
“…[22] Comprehensive nursing based on the concept of evidence-based nursing can dialectically understand the problems existing in clinical practice and propose humanized and targeted nursing measures through analysis and summary, which are of important for reducing patients' pain and improving their quality of life. [23] In this study, the incidence of postoperative pressure ulcers was considerably lower in the observation group than in the control group, indicating that perioperative comprehensive nursing care can significantly reduce the incidence of pressure ulcers in prone patients. Evaluation of the patient risk factors for pressure ulcers is a key factor in their prevention.…”
Section: Discussionmentioning
confidence: 49%
“…In recent years, bibliometric analyses have taken place frequently in the field of nursing 26,27. However, no similar bibliometric analysis study has been published on holistic nursing, which is one of the main building blocks of nursing practices.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, bibliometric analyses have taken place frequently in the field of nursing. 26,27 However, no similar bibliometric analysis study has been published on holistic nursing, which is one of the main building blocks of nursing practices. This study, which is the first bibliometric analysis study available on holistic nursing, unfortunately, has some limitations.…”
Section: Limitations and Superioritymentioning
confidence: 99%
“…Hot topics characterize major problems in a certain field, and they allow researchers to develop an insight into the research trends (Liu et al, 2021). Keyword analysis has revealed that hot topics in leadership and care are “evidence‐based practice” and “patient safety.” Evidence‐based practice is key to improving healthcare quality and patient outcomes and is a fundamental competence that ensures patient safety for nurses (ALFadhalah & Elamir, 2022; Unal & Teskereci, 2021). Studies have shown an important relationship between leadership behaviours and evidence‐based practice and patient safety (Labrague et al, 2021; Parr et al, 2021).…”
Section: Discussionmentioning
confidence: 99%